Comparison of Neoadjuvant Chemo-Hormonal Therapy Versus Hormonal Therapy in Locally Advanced Prostate Cancer - Fahad Mehmood Khokhar, Shah Jahan-Ur-Rehman, Kamran Zaidi, Saad Ali Baloch, Muhammad Usman Anwar, Muhammad Faraz Latif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prostate cancer cells depend on testosterone to grow and spread. Hormone therapy aims to decrease testosterone levels, either by directly reducing testosterone production or by inhibiting the action of testosterone on cancer cells. It can be used alone or in combination with other treatments like radiotherapy, chemotherapy, immunotherapy and surgery. Chemotherapy uses drugs to destroy cancer cells. Hormone therapy is combined with chemotherapy to offer more effective control of prostate cancer in advanced cases. Early, aggressive treatment approaches such as neoadjuvant hormonal therapy has been explored as a way to improve long-term outcomes in locally advanced prostate cancer. Objective: To compare the neoadjuvant chemohormonal therapy versus hormonal therapy in locally advanced prostate cancer. Methodology: This comparative study was conducted at Urology Department, Jinnah Hospital Lahore from 1st July 2022 to 30th September 2023. A total of 200 patients were compared for the outcomes of locally advanced prostate cancer and each group comprised equal number of patients. Group A patients were treated with chemotherapeutic agent docetaxel, dosage 75mg/m2 IV over 1 hour every 3 weeks; prednisone 5mg orally 2 times a day and hormonal agent bicalutamide 50 mg once daily. Group B patients were treated only with hormonal agent bicalutamide 50 mg once daily. The mean therapy time was taken as 3.7 months. The diagnosis was based on the chest and abdomen computed tomography and pelvic magnetic resonance imaging as well as bone scanning. The clinical tumor and nodal staging was based on the magnetic resonance imaging or computed tomography and results were in accordance to the TNM staging classification. Male patients with a confirmed diagnosis of prostate cancer through biopsy, stage pT3b–pT4 disease, ISUP grade ≥4, or a post-prostatectomy prostate specific antigen level ≥0.2 ng/ml were also included. The exclusion criteria included histological subtypes of prostate cancer with small cell neuroendocrine or sarcomatous differentiation, history of prior treatment including prostate surgery, radiotherapy, chemotherapy, or immunotherapy, diagnosis of other malignancies or evidence of disease progression, cases with metastatic changes, hypersenstivity of drugs, immunocompromised, hepatic and renal impaired patients were excluded. The results of both therapies were compared in terms of primary and secondary outcomes. Results: The mean age of both group patients was almost similar as 67.15±3.1 and 69.1±2.3 year. The mean PSA levels before any intervention was also reported to be insignificantly variant within both groups (52.2±20.5 and 56.5±21.0 ng/ml) respectively. The mean therapy time was taken as 3.7 months. However, within the comparison of pre-treated with post-treatment results, a highly significant improvement in T staging was observed in group A with a substantial decrease from pre-treatment, 50% T3b staging to 36% in post-treatment through neoadjuvant chemohormonal therapy. The post-treatment response presented a significant decrease in the mean testosterone level in group A compared to group B. Further post-treatment, the pathological response grade presented better improvement in group A as compared to group B. The pathological down staging of group A was presented as in 61% cases in comparison to only 35% in group B. The PSA complete response was observed in 67% of group A patients in comparison to 35% in group B. Moreover the comparison of the biochemical recurrence-free survival (bRFS) rate, this study presented a significant increase in survival rate with neoadjuvant chemohormonal therapy than hormonal therapy. Conclusion: Neoadjuvant chemohormonal therapy is more efficient than hormonal treatment in terms of the biochemical recurrence-free survival rates, improved pathological downstaging outcomes and more substantial prostate specific antigen reduction in patients with locally advanced prostate cancer. Keywords: Neoadjuvant chemohormonal therapy, Hormonal therapy, Locally advanced prostate cancer, Biochemical recurrence